2011
DOI: 10.1111/j.1399-5448.2010.00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk factors as apolipoprotein B, triglyceride/HDL-cholesterol ratio and C-reactive protein, in adolescents with and without obesity: cross-sectional study in middle class suburban children

Abstract: Even when the frequency of OB, OW, and MS in adolescents was low, those subjects presented an atherogenic lipoprotein. These findings emphasize the importance to evaluate cardiovascular risk factors in adolescents to assess strategies to prevent future disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
4
32
0
2
Order By: Relevance
“…Recently, some studies have reported that even in the pediatric population, the TG:HDL-C ratio is related to IR and chronic inflammation (10,12,23). Accordingly with these findings, our results confirm the already reported association between TG:HDL-C ratio, IR status, and chronic inflammation, and highlight the value of the TG:HDL-C Significant values by post-hoc analysis: *3rd tertile vs 1st tertile and † 3rd tertile vs 2nd tertile.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, some studies have reported that even in the pediatric population, the TG:HDL-C ratio is related to IR and chronic inflammation (10,12,23). Accordingly with these findings, our results confirm the already reported association between TG:HDL-C ratio, IR status, and chronic inflammation, and highlight the value of the TG:HDL-C Significant values by post-hoc analysis: *3rd tertile vs 1st tertile and † 3rd tertile vs 2nd tertile.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we showed that the TG:HDL-C ratio is an additional independent factor associated with cIMT, therefore providing a further line of evidence for a role of the TG:HDL-C ratio in the cardiovascular risk that was able to discriminate subjects with more marked signs of early atherosclerosis as indicated by higher values of cIMT. It needs to be acknowledged that in our study population, values of the TG:HDL-C ratio were not particularly high when compared with previous studies performed in obese youth (10,23). However, our study population was made only of prepubertal and Caucasian children, and this could explain differences in TG:HDL-C compared with other studies, where also adolescents and a mixture of ethnic groups were studied.…”
Section: Clinical Studymentioning
confidence: 65%
“…In a large series of 26000 overweight children, concentrations of one or more of the lipids were abnormal in 32%: total cholesterol in 14.1%, LDL-C in 15.8%, HDL-C in 11.1%, and triglycerides in 14.3% of those in whom data were available. [53] In a series of 943 school-going adolescents, Musso et al [68] reported significant differences in the levels of triglycerides (73 mg/dl vs 90 mg/dl; P<0.001), and HDL-C (52 mg/dl vs 47 mg/dl; P<0.001) between non-overweight and overweight groups.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…Previous research has demonstrated its positive associations with adverse cardiometabolic risk factor profiles, metabolic syndrome and prediction of incident T2DM or its complications (Di Bonito et al, 2012;He et al, 2012;Cordero et al, 2008;Musso et al, 2011;Zoppini et al, 2011;Gaziano et al, 1997;Giannini et al, 2011;Bittner et al, 2009;Li et al, 2008;Quijada et al, 2008;McLaughlin et al, 2003;Fan et al, 2007). This may occur as the triglyceride-to-HDL cholesterol ratio demonstrates an association with insulin resistance (Giannini et al, 2011;Li et al, 2008;Quijada et al, 2008;McLaughlin et al, 2003;Fan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The triglyceride-to-HDL cholesterol ratio has been investigated recently for various potential clinical uses in adult and paediatric populations (Di Bonito et al, 2012;He et al, 2012;Cordero et al, 2008;Musso et al, 2011;Zoppini et al, 2011;Gaziano et al, 1997;Giannini et al, 2011;Bittner et al, 2009;Li et al, 2008;Quijada et al, 2008;McLaughlin et al, 2003;Fan et al, 2007). Previous research has demonstrated its positive associations with adverse cardiometabolic risk factor profiles, metabolic syndrome and prediction of incident T2DM or its complications (Di Bonito et al, 2012;He et al, 2012;Cordero et al, 2008;Musso et al, 2011;Zoppini et al, 2011;Gaziano et al, 1997;Giannini et al, 2011;Bittner et al, 2009;Li et al, 2008;Quijada et al, 2008;McLaughlin et al, 2003;Fan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%